Predictors of favorable results in pulmonary tuberculosis treatment (Recife, Pernambuco, Brazil, 2001-2004) - Sassaki, Cinthia Midori; Scatena, Lucia Marina; Gonzales, Roxana Isabel Cardozo; Ruffino-Netto, Antonio; Hino, Paula; Villa, Tereza Cristina Scatena (Revista da Escola de Enfermagem da USP, 2010)
Based on data available in the Information System for Notifiable Diseases, predictive factors of favorable results were identified in the treatment of pulmonary tuberculosis, diagnosed between 2001 and 2004 and living in Recife-PE, Brazil. Uni- and multivariate logistic regression methods were used. In multivariate analysis, the following factors remained: Age (years), 0 to 9 (OR=4.27; p=0.001) and 10 to 19 (OR=1.78; p=0.011), greater chance of cure than over 60; Education (years), 8 to 11 (OR=1.52; p=0.049), greater chance of cure than no education; Type of entry, new cases (OR=3.31; p